EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH DALAM PELAKSANAAN KURIKI]LUM 2OO4 PADA SMA PILOTING DI DAERAH ISTIMEWA YOGYAKARTA - Handayani, Trikinasih; Susilo, M. Joko (Prodi Pendidikan Biologi FKIP UNS, 2006)
AbstractThis research was aimed to know the ffictivenness of headmaster's leadership toward theimplementation of curiculum 2004. This research focused on the the integity of the headmaste, his ability onovercoming the institution's problems and his leadership style and related them with the leadership'seffectivenessin in carrying the implementation of the curiculum 2004. This research wqs carried out at SMAN 7fogyakarta, SMAN 11 iogyakarta, SMAN Sewon and SMAN Kalasan. The data collected by anquette wereanalyzed by double regression and Pearson's correlation uslng SPSS release 10. Intepretation was then madedescriptivelly.The results showed that all, the integrity, ability to solve the institation's problems, and the ladershipgtyle of the headmaster, together, afficted the leadership's ffictiveness of the headmaster duringimplementation of curiculum 2004.Key words: Curiculum 2004, imptementation, leadership ffictivenes of the headmaster